Alkaline activation of high-calcium ash and iron ore tailings and their recycling potential in building materials - Bezerra, Augusto Cesar da Silva; França, Sâmara; Magalhães, Luciano Fernandes de; Carvalho, Maria Cristina Ramos de (Ambiente Construído, 2019)
Alkali-activated materials are agglomerates obtained from the alkaline activation of aluminum- and silicone-rich precursors. The most popular precursors for this type of activation are low-calcium fly ashes, blast furnace slag, and metakaolin. However, both high-calcium ashes (HCAs) and iron ore tailings (IOTs) are interesting wastes that can be investigated as precursors because of their available volume and environmental impact during their final deposition. Therefore, by performing tests of compressive strength, FTIR spectrometry and scanning electron microscopy, we sought to identify the products formed during HCA and IOT activation without thermal treatment. Nine mortar formulations with different HCA and IOT proportions were developed using sodium hydroxide and sodium silicate as activators. Thus, using FTIR spectrometry, we observed the reaction between the industrial wastes. Additionally, the compressive strength result suggested that the material could be used as compressed blocks in masonry walls for the development of more environmentally friendly building materials, which would mitigate the impact of waste disposal and convert industrial solid waste into value-added products.